Telegram sebagai Medium Alternatif dalam Proses Pengajaran dan Pembelajaran di Rumah (PdPR): Telegram as an Alternative Medium in the Teaching and Learning Process at Home (PdPR) - Mohd Rusli, Nur Farahkhanna; Mohd Rofizi, Fatin Natasya; Abu Bakar, Nurulaisyah (Online Journal for TVET Practitioners, 2022)
The aim of this study is to explain the use of Telegram application as an alternative medium in the teaching and learning process at home. This study is a descriptive qualitative study. Data of the study were obtained through library research with the aids of instruments such as notebooks and written sources such as journals, scientific books, dissertations and articles related to the scope of the study. The data obtained will be used to help provide justification to explain the benefits of Telegram application as an alternative medium in the teaching and learning process at home. The results show that the Telegram application has the advantage which is user-friendly application, helps teachers and students achieve learning objectives and encourages collaborative learning among students. In terms of implications, this study can highlight the benefits of using Telegram application as one of the alternative mediums that can be used in the online teaching and learning process.